STUDI LITERATUR MENGENAI INTEGRASI NILAI-NILAI ETIKA BISNIS ISLAM DALAM PRAKTIK CORPORATE SOCIAL RESPONSIBILITY PADA LEMBAGA KEUANGAN SYARIAH DI ERA MODERN - Fauziah Mutiara Leste; Ahmad Habibi; Muhammad Iqbal Fasa (Jurnal Riset Multidisiplin Edukasi, 2025)
The global Islamic finance industry is experiencing exponential growth that demands the integration of corporate social responsibility based on Islamic ethical values. This research aims to analyze the conceptualization of Islamic business ethics values within the maqasid al-shariah framework, evaluate CSR implementation practices, identify challenges, and analyze implications for the sustainability of Islamic financial institutions. Library research method with qualitative-descriptive analytical approach was employed through content analysis of academic literature from 2020-2025. The results indicate that Islamic Corporate Social Responsibility (ICSR) based on maqasid al-shariah has fundamental differences from conventional CSR through the integration of tawhid, justice, amanah, and ihsan principles in economic empowerment programs, Islamic financial literacy, and social welfare. Internal challenges include limited organizational capacity and complexity of sharia compliance, while external challenges encompass the absence of global standardization and diverse stakeholder expectations. The integration of Islamic ethical values provides positive implications for sustainable performance, competitive advantage, and social legitimacy of Islamic financial institutions. Strengthening human resource capacity, developing holistic measurement instruments, and standardizing ICSR are necessary to optimize contributions to sustainable development.